Нелегальна міграція та нелегальний мігрант: зниження актуальності державного дозволу (міжнародний аспект) - Крут, К. О.; Krut, K. O. (Правові новели. - 2023. - № 21. - С. 102-106, 2023)
Розкрито поняття нелегального мігранта, визначено його правовий статус і законні права, як головного «учасника» нелегальної міграції у міжнародному контексті. Оскільки кожна держава визначає для себе межі та особливості правового статусу нелегального мігранта, розглянуто якими правами наділений нелегальний мігрант, та на які різновиди поділяється з огляду на практику міжнародного законодавства.

This article is about the illegal migrant, the determination of his legal status and legal rights, as the main «participant» of illegal migration in the international context. Since each state defines for itself the limits and peculiarities of the legal status of an illegal migrant, we considered what rights an illegal migrant is entitled to and what types they are divided into based on the practice of international law. The state and legislation of European countries rarely define illegal migration. Instead, we see that illegal migration is often a residual category of persons who do not fall under the definition of legal or legal migration. In reality, illegal migration is becoming more of an abstract idea, couched in policy statements and measures than in a coherent legal framework. Moreover, we can come to the assumption that the states themselves are interested in presenting their policies as a rational and legitimate response to the pressure of migration flows, because certain categories of migration are essentially state constructions. The category of illegal migration is a good example, as illegal migration is by definition a by-product of laws enacted to control migration and labor market needs. The absence of state authorization or consent places them in the realm of illegality, thereby rendering their presence illegitimate. This means that European states themselves choose and create restrictions on these categories of persons. Illegal migration is a good example, as illegal migration is by definition a by-product of laws enacted to control migration and labor market needs. As Castles and Davidson have aptly pointed out, cautioning against the claim that «illegal migration is often tacitly permitted or even encouraged» (by governments and employers) simply because illegal migrants are disenfranchised and easily exploited. The above article just described the rights that a person with the status of an illegal migrant is entitled to.

Раскрыто понятие нелегального мигранта, определен его правовой статус и законные права как главного «участника» нелегальной миграции в международном контексте. Поскольку каждое государство определяет для себя границы и особенности правового статуса нелегального мигранта, рассмотрены какими правами наделен нелегальный мигрант, и на какие виды делится с учетом практики международного законодательства.
Illegal migration and the illegal migrant: decreasing relevance of the state permit (international aspect)
Keywords: нелегальна міграція; illegal migration; нелегальная миграция; нелегальний мігрант; illegal migrant; нелегальный мигрант; державна політика; state policy; государственная политика; міжнародний аспект; international aspect; международный аспект; боротьба з нелегальною міграцією; fight against illegal migration; борьба с нелегальной миграцией